Rutting potential of hot mix asphalt in variable conditions - Sheikh, Salman Ullah (2007)
Flexible pavements are designed to withstand structural and functional failures. Rutting is a structural defect associated with functional implications. Rutting is mainly caused by wheel loads and accelerated by environmental factors. Although rutting is contributed by all the five layers in flexible pavement (subgrade, subbase, road base bindercoarse and wearing coarse) the behaviour of wearing coarse is least understood and contributes significant effect to the overall pavement. The objective of this study is the identify the rutting behaviour of wearing coarse subjected to repetitive vehicle load and exposed to different environments. This study is carried on scaled down pavement stretch of 22.6m consisting of two mixes ACW14 and ACW20 which is then subjected to repetitive load with exposure to different environmental effects such as wet stretch, heat condition, spillage of petrol, diesel and cooking oil. For each selected pavement, section rut is measured after 50 cycles of the wheel track which has a weight of 280kg. A multivariate regression analysis is carried out to determine the relationship of rut depth and number of wheel track passes. The results show exposure to petrol and diesel has a very detrimental effect to the pavement.